Gamfication dalam Evaluasi Pembelajaran untuk Meningkatkan Hasill Belajar dengan Aplikasi Kahoot Mata Pelajaran Informatika SMA Negeri 14 Maros - Sunarti Rasdin; Ananda Amalia Rahma; Nasir Nasir; Sadriana Ayu; Muhammad Wahyu (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2024)
This research is clossroom action research (Classroom Action research) which aims to deretmine tha improvement in student learning outcomes in the informatics subject class X.1 SMA Negeri 14 Maros. The research subjects were students in class X.1 of SMA Negeri 14 Maros for the 2023/2024 academic year with a tital of 36 students. This research was conducted in two cycles and each cycle consisted of 4 meetings. The results of this research show that the application of kahoot game-based media can increase student activity and learning outcomes in informatics subjects. Quatitative analysis shows that learning outcomes in the initial test were 33.33%, in cycle i there was an increase of 55.55% and then in cycle II it became 88.88%. This means that there is a significant increase in student learning outcomes.